2021
DOI: 10.37575/b/med/2267
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mothers' Knowledge about Autism: Saudi Arabia

Abstract: Autism is an advanced neurogenic disease condition with specific neurodevelopmental characteristics and deficiency in social relations and interaction, as well as limited rhythmic and stereotyped patterns of actions that habitually arise in the toddler stage of life. Mothers of children with autism were found to have greater levels of childcare-associated stress. This study aims to determine mothers' general knowledge of autism. A cross-sectional study was conducted among the mothers of autistic children in Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…Level of education and the mother's job. This result agreed with Mousa O., et al [27] who found that there was a highly statistically significant between total knowledge and the parent's age but there wasn't any statistical significance between other socio demographic characteristic of the parent having children with autism.…”
Section: Kousha Et Al [22]supporting
confidence: 90%
See 1 more Smart Citation
“…Level of education and the mother's job. This result agreed with Mousa O., et al [27] who found that there was a highly statistically significant between total knowledge and the parent's age but there wasn't any statistical significance between other socio demographic characteristic of the parent having children with autism.…”
Section: Kousha Et Al [22]supporting
confidence: 90%
“…An increase in ASD prevalence is visible CDC ., [12] Care givers for autistic children were found to have a low level of knowledge about the disease. Because of the inadequate parents knowledge this have an impact of the parent practices and attitude toward their children with autism Mousa et al, [27].…”
Section: Introductionmentioning
confidence: 99%
“…They reported that more than half of their participants, 52.6% were poor knowledge with nearly the same weakness areas. A recent Saudi study was conducted among autistic children mothers in Al Ahsa, Saudi Arabia, byMousa et al, (2021) found that 69.8% of all mothers had a low knowledge level and lacked perception about ASD. Another Saudi study was conducted byHaimour & Obaidat, (2013), their study revealed that general education teachers had a weak knowledge level about ASD while special education teachers had a good knowledge level.…”
mentioning
confidence: 99%